Benchmarking the nutrient composition and labelling practices of commercially produced ready‐to‐eat purées and meals for older infants and young children across seven Southeast Asian countries - Eleonora Bassetti; Jessica Blankenship; Jessica M. White; Anzélle Mulder; Diane Threapleton; Alissa M. Pries (Wiley, 2023)
Abstract Commercially produced complementary foods (CPCF), including ready‐to‐eat CPCF purées and meals, are gaining popularity among caregivers of older infants and young children (IYC) as a convenient alternative to home‐prepared foods in low and middle‐income countries. However, there is growing concern regarding the suitability of these products for older IYC, as they can contain high levels of sugar and/or sodium. Given the rapidly evolving market in Southeast Asia, it is crucial to monitor the appropriate composition and promotion of CPCF in the region. This study examined the nutrient composition and labelling practices of CPCF purées and meals sold in 2021 in the capital cities of seven Southeast Asian countries: Phnom Penh (Cambodia), Jakarta (Indonesia), Manila (Philippines), Bangkok (Thailand), Vientiane (Lao PDR), Hanoi (Viet Nam), Kuala Lumpur (Malaysia). The study adapted a nutrient profiling model from the WHO Regional Office for Europe to determine the proportion of products suitable for promotion for older IYC. The proportion of CPCF purées and meals that would require a high sugar front‐of‐pack warning based on the percentage energy from total sugar was also determined. Of the 459 CPCF purées/meals assessed, only 37.7% of the products met all nutrient composition requirements and none met all labelling requirements. In addition, most CPCF purées and meals were identified as having high total sugar content. To ensure that older IYC consume appropriate CPCF products, Southeast Asian countries need to implement and enforce regulations concerning the nutrient composition and labelling practices of CPCF purées and meals.